Advances in solar evaporator materials for freshwater generation. Issue 42 (8th October 2019) - Cao, Sisi; Jiang, Qisheng; Wu, Xuanhao; Ghim, Deoukchen; Gholami Derami, Hamed; Chou, Ping-I.; Jun, Young-Shin; Singamaneni, Srikanth
Abstract : To alleviate the scarcity of clean water, solar steam generation, which utilizes the green and abundant resources of Earth, has attracted considerable attention and been recognized as a sustainable technology to purify seawater and wastewater. Abstract : To alleviate the scarcity of clean water, solar steam generation, which utilizes the green and abundant resources of Earth, has attracted considerable attention and been recognized as a sustainable technology to purify seawater and wastewater. Within the past five to seven years, building on remarkable advances in the synthesis of nanoscale photothermal materials, significant progress has been made in the design and fabrication of solar evaporators. Here, we comprehensively review the materials and structures of the three key components of solar evaporators: solar absorbers, substrates ( i.e., support layers), and water collectors towards efficient harvesting of sunlight, thermal management, water transportation, interfacial evaporation, and collection. In particular, we discuss the design principles of water collectors for solar-driven evaporation, which are in the early stages of development at present. Furthermore, bio-inspired water collectors provide exciting opportunities for the design and realization of efficient water harvesting from solar steam. Finally, we introduce photothermal-enhanced membrane distillation (PMD), a promising alternative technique involving solar-driven interfacial evaporation for producing clean water. PMD combines solar energy and membrane distillation, which facilitates efficient water purification and collection. In this review, we discuss the design guidelines and recent development of this photothermal-enhanced water purification. This review provides useful insights into the material choice and structure optimization to realize enhanced solar evaporators towards freshwater generation.